Efektivitas Pembelajaran Jarak Jauh Dalam Perspektif Mahasiswa - Hasanuddin, Hasanuddin (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
This research was conducted to determine the effectiveness of distance learning from the perspective of students such as the material provided by the lecturer, understanding of the material, obstacles in participating in distance learning, and the learning model carried out. This study uses a descriptive survey method, the research sample is students from Bhayangkara University, Jakarta Jaya (Ubhara Jaya). Data collection techniques using a questionnaire. The findings in this study, 64.1% of students disagree with distance learning, according to students distance learning is not effective in the teaching and learning process, and 35.9% agree. Those who agree with distance learning generally state that this is a way to stop the spread of Covid 19. When asked about the understanding of the lecture material delivered by the lecturer through distance learning, 72.5 students found it difficult because the question-and-answer process was less effective. Constraints experienced by students during distance learning, 43.1% were caused by unstable signals, 37.7% answered that there were no problems, and 19.2% answered that they sometimes experienced signal disturbances. Regarding student spending during distance learning, 43.8% said they were not more efficient than offline lectures, 41.1% said there were savings.